Incidence trends and disparities in Helicobacter pylori related malignancy among US adults, 2000–2019 - Lai, Yafang; Shi, Haoting; Wang, Zixin; Feng, Yibo; Bao, Yujia; Li, Yongxuan; Li, Jinhui; Wu, Anhao (Frontiers in Public Health, 2022)
Background Helicobacter pylori (H. pylori) is closely related to the carcinogenesis of gastric cancer (GC) and gastric non-Hodgkin lymphoma (NHL). However, the systemic trend analysis in H. pylori-related malignancy is limited. We aimed to determine the national incidence trend in non-cardia GC, cardia GC, and gastric NHL in the US during 2000–2019. Method In this population-based study, we included 186,769 patients with a newly diagnosed H. pylori-related malignancy, including non-cardia GC, cardia GC, and gastric NHL from the Surveillance, Epidemiology, and End Results (SEER) Registry from January 1, 2000 to December 31, 2019. We determined the age-adjusted incidence of three H. pylori-related malignancies respectively. Average annual percentage change (AAPC) in 2000–2019 was calculated to describe the incidence trends. Analyses were stratified by sex, age, race and ethnicity, geographic location and SEER registries. We also determined the 5-year incidence (during 2015–2019) by SEER registries to examine the geographic variance. Results The incidence in non-cardia GC and gastric NHL significantly decreased during 2000–2019, while the rate plateaued for cardia GC (AAPCs, −1.0% [95% CI, −1.1%−0.9%], −2.6% [95% CI, −2.9%−2.3%], and −0.2% [95% CI, −0.7%−0.3%], respectively). For non-cardia GC, the incidence significantly increased among individuals aged 20–64 years (AAPC, 0.8% [95% CI, 0.6–1.0%]). A relative slower decline in incidence was also observed for women (AAPC, −0.4% [95% CI, −0.6%−0.2%], P for interaction < 0.05). The incidence of cardia GC reduced dramatically among Hispanics (AAPC, −0.8% [95% CI, −1.4%−0.3%]), however it increased significantly among nonmetropolitan residents (AAPC, 0.8% [95% CI, 0.4–1.3%]). For gastric NHL, the decreasing incidence were significantly slower for those aged 20–64 years (AAPC, −1.5% [95% CI, −1.9–1.1%]) and Black individuals (AAPC, −1.3% [95% CI, −1.9–1.1%]). Additionally, the highest incidence was observed among Asian and the Black for non-cardia GC, while Whites had the highest incidence of cardia GC and Hispanics had the highest incidence of gastric NHL (incidence rate, 8.0, 8.0, 3.1, and 1.2, respectively) in 2019. Geographic variance in incidence rates and trends were observed for all three H. pylori-related malignancies. The geographic disparities were more pronounced for non-cardia GC, with the most rapid decline occurring in Hawaii (AAPC, −4.5% [95% CI, −5.5–3.6%]) and a constant trend in New York (AAPC 0.0% [95% CI, −0.4–0.4%]), the highest incidence in Alaska Natives, and the lowest incidence among Iowans (14.3 and 2.3, respectively). Conclusion The incidence of H. pylori-related cancer declined dramatically in the US between 2000 and 2019, with the exception of cardia GC. For young people, a rising trend in non-cardia GC was noted. Existence of racial/ethnic difference and geographic diversity persists. More cost-effective strategies of detection and management for H. pylori are still in demand.